2022
DOI: 10.1002/jcc.26882
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of high dimensional free energy landscapes by a combination of temperature‐accelerated sliced sampling and parallel biasing

Abstract: Temperature‐accelerated sliced sampling (TASS) is an enhanced sampling method for achieving accelerated and controlled exploration of high‐dimensional free energy landscapes in molecular dynamics simulations. With the aid of umbrella bias potentials, the TASS method realizes a controlled exploration and divide‐and‐conquer strategy for computing high‐dimensional free energy surfaces. In TASS, diffusion of the system in the collective variable (CV) space is enhanced with the help of metadynamics bias and elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 109 publications
(220 reference statements)
0
12
0
Order By: Relevance
“…Thus, the method takes advantage of metadynamics simulations and is expected to give an overview of the relevant free energy minima states through the controlled exploration of phase space. Nair et al showed a similar implementation; 68 this group also reported similar high-temperature controlled sampling methods, such as temperature accelerated sliced sampling (TASS), 71 and parallel bias TASS (PBTASS), 70 etc. , which were applied to antibiotic permeation by Kleinekathöfer et al 72…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, the method takes advantage of metadynamics simulations and is expected to give an overview of the relevant free energy minima states through the controlled exploration of phase space. Nair et al showed a similar implementation; 68 this group also reported similar high-temperature controlled sampling methods, such as temperature accelerated sliced sampling (TASS), 71 and parallel bias TASS (PBTASS), 70 etc. , which were applied to antibiotic permeation by Kleinekathöfer et al 72…”
Section: Methodsmentioning
confidence: 91%
“…48,67,68 The method of combining umbrella sampling and metadynamics biases for the sampling of high-dimensional free energy surfaces was proposed by Filizola and co-workers 69 and by Nair and co-workers. 68 We propose a modified version of this method where the metadynamics bias is replaced by the parallel bias metadynamics bias, as discussed in the PBTASS 70 method. Details of the theory of the controlled sampling approach and the reweighting procedure are discussed in Section II of the ESI.…”
Section: Equilibration and Simulationmentioning
confidence: 99%
“…A large number of collective variables (CVs) can be considered for enhanced sampling. Various chemical and biological reactions have already been studied using the TASS method. …”
Section: Introductionmentioning
confidence: 99%
“…To reconcile resource requirements with the exploration of microscopic complexities, conventional workflows are increasingly complemented by hybrid enhanced sampling methods and data-driven techniques. [37][38][39][40][41][42][43] With this motivation, our recent contribution, namely the development of the Expectation Maximized MD (EMMD), offers a highly efficient platform for the estimation of maximum likely free energy barriers without biasing the simulations. [44] Unlike conventional approaches, this method avoids direct sampling of the transitions.…”
Section: Introductionmentioning
confidence: 99%